Brain functional connectivity in patients with hyperthyroidism after anti‐thyroid treatment. (14th December 2021) - Kumar, Mukesh; Singh, Sadhana; Rana, Poonam; Modi, Shilpi; Sekhri, Tarun; Kanwar, Ratnesh; D'Souza, Maria; Khushu, Subash
Abstract: Thyroid disease is known to affect brain metabolism and cognitive function, although the recovery of thyroid‐induced brain functional changes after treatment remains unclear. We aimed to investigate the alteration in brain functional connectivity and its correlation with neuropsychological variables in hyperthyroid patients before and after anti‐thyroid treatment using a resting‐state functional magnetic resonance imaging (rsfMRI) technique. This is a follow‐up rsfMRI study of previous work that showed impaired brain functional connectivity in hyperthyroid patients compared to healthy controls. We included rsfMRI and neuropsychological data from 21 hyperthyroid patients out of an original cohort of 28 patients, before and after anti‐thyroid treatment for 30 weeks. Functional connectivity analysis and neuropsychological scores were compared using paired t tests in patients at baseline and at follow‐up. Patients showed an improvement in some of the memory ( p < .05) and executive, visuospatial and motor ( p < .001) functions after treatment, and also showed increased functional connectivity in the regions of the right fronto‐parietal network, left fronto‐parietal network, and default mode network (DMN) ( p < .05). At follow‐up, the functional connectivity of the right fronto‐parietal network showed a significantly positive correlation with the recognition of objects memory score. The overall findings suggest that anti‐thyroid treatment with carbimazole improves the functional connectivity within some of the resting state networks in the hyperthyroid patients, whereas the remaining networks still show impairment. Abstract : The present study demonstrates an improvement in resting state networks functional connectivity and cognitive function in hyperthyroid patients after anti‐thyroid treatment.